(untitled) (Conferencea, 2022)
This article is concerned with the study of gender aspect in the process of translation. The study focuses on the investigation of the impact of author’s gender and cultural background on translation process. To be more specific, the article is aimed to explore the linguacultural distinctive features of translated work by male and female translators. Previous researches and studies in this area of investigation have been gathered and analyzed. Several points of the issue have been taken into consideration and concluded that there are a number of linguacultural distinctive differentiations in the translation process done by male and female translators.